2009
DOI: 10.1002/mrd.21137
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from biodiversity—the value of nontraditional species to advance reproductive science, conservation, and human health

Abstract: SUMMARY Reproduction is quintessential to species survival. But what is underappreciated for this discipline is the wondrous array of reproductive mechanisms among species—variations as diverse as the morphology of the species themselves (more than 55,000 vertebrate and 1.1 million invertebrate types). We have investigated only a tiny fraction of these species in reproductive science. Besides the need to fill enormous gaps in a scholarly database, this knowledge has value for recovering and genetically managin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
81
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(83 citation statements)
references
References 73 publications
(36 reference statements)
0
81
0
Order By: Relevance
“…In conclusion, study results underscored the importance of species diversity in fundamental reproductive phenomena, as has been emphasized recently in the contexts of biological conservation and human health [82]. We predict that understanding the unique mechanisms of energy production in felid spermatozoa will facilitate increased efficiency of assisted reproductive technologies that have been used for producing offspring in wild felids [83,84].…”
Section: Discussionmentioning
confidence: 55%
“…In conclusion, study results underscored the importance of species diversity in fundamental reproductive phenomena, as has been emphasized recently in the contexts of biological conservation and human health [82]. We predict that understanding the unique mechanisms of energy production in felid spermatozoa will facilitate increased efficiency of assisted reproductive technologies that have been used for producing offspring in wild felids [83,84].…”
Section: Discussionmentioning
confidence: 55%
“…Some successful conservation efforts could even help to consider that plastic can save species. There actually are many examples of species that are not necessarily threatened by plastic in their natural habitat but have been rescued from extinction, have been restored in captivity, and are now being reintroduced in the wild (Wildt et al, 2010) by taking advantage of plastic materials at each critical step (Figure 2). …”
Section: Discussionmentioning
confidence: 99%
“…Although many of the observed effects were consistent with studies of other species, several unique responses were observed in feline oocytes, including the stimulation of meiosis by forskolin. Such species-specific effects emphasise the need for comparative studies, especially in taxa like Carnivora, where a variety of reproductive mechanisms exist and basic information concerning gamete and early embryo biology is limited (Desmarais et al 2004;Songsasen and Wildt 2007;Bateman et al 2009;Wildt et al 2010). Such studies will expand our understanding of reproductive biology, as well as allow for the development of alternative model species for studies of various reproductive processes.…”
Section: Discussionmentioning
confidence: 99%